A study of the adaptation of cereals and forage-crops in Kansas - Thompson, Charles L. (My University, 1905)
Introduction: The object of this study is to determine what crops are best adapted to the conditions existing in the different sections of the state. The accompanying tables which have been compiled from data found in the "Fourteenth Biennial Report of the Kansas State Board of Agriculture," give the acreage and value per acre in each county of the state for the year 1904, of each of the several more important crops, viz.; wheat, corn, oats, flax, sorghum, millet, kafir-corn, alfalfa and prairie hay. As alfalfa is classed with other tame grasses it is impossible in most cases to determine its value per acre. Wheat - As spring wheat is not raised to any great extent, and only in a few of the western counties, it has been entirely ignored in this paper. Wheat is grown in each and every county in the ;state, the entire acreage for 1904 being 5,816,495 acres, with an average value of $8.75 per acre, or a total value of $51,149,917.12. The Central and west central portion of the state shows the greatest acreage and the greatest value per acre. Sumner County heads the list with 294,434 acres, yielding an average value of p10.66 per acre. Barton County is second, with 262,667 acres and an average value per acre of $10.40. Harper County comes third, with 171,240 acres, and an average value of 13.94 per acre. Wheat seems to be especially adapted to Kansas soil and climate and there is a growing tendency, especially in the western portion of the state, to increase the acreage at the expense of the other cereals. In the last, four years the acreage for the state has been increased over 900,000 acres. It is true however, as must necessarily be the case where crop after crop is taken from the land and nothing given in return, that the yield per acre is steadily decreasing.
Citation: Thompson, Charles L. A study of the adaptation of cereals and forage-crops in Kansas. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Adaptation of Wheat; Adaptation of Corn; Adaptation of Oats; Theses